A note on the justification of the eddy current model in electrodynamics. (3rd October 2017) - Pauly, Dirk; Picard, Rainer
Abstract : The issue of justifying the eddy current approximation of Maxwell's equations is reconsidered in the time‐dependent setting. Convergence of the solution operators is shown in the sense of strong operator limits.